Beating Inflation With Real Estate - Harney, Kenneth R. (New York Random House, 1979)
Beating Inflation With Real Estate. It is intended to be to be an introdactory, plan-language guide to the fundamental of investing in rental houses, land, second mortgages, vacation rental, property and related areas for the many people whove never done it before but would like to try their hand. Author tried to keep real estate jargon to a minimum and have intertionally ommited the cash-flow charts and comparative-yield computations that fill more academic and advanced work in the field.
Keywords: Economics